2013
DOI: 10.1093/gbe/evt064
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Retrotransposons Assessed by High-Throughput Sequencing in Wild Relatives of Wheat

Abstract: Transposable elements (TEs) represent a major fraction of plant genomes and drive their evolution. An improved understanding of genome evolution requires the dynamics of a large number of TE families to be considered. We put forward an approach bypassing the required step of a complete reference genome to assess the evolutionary trajectories of high copy number TE families from genome snapshot with high-throughput sequencing. Low coverage sequencing of the complex genomes of Aegilops cylindrica and Ae. genicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 68 publications
(88 reference statements)
2
41
2
Order By: Relevance
“…Though several studies report recent LTR-retrotransposon bursts in related grasses (Piegu et al 2006;Bennetzen et al 2012;Senerchia et al 2013), we did not detect a large amount of recent activity in the Sorghum reference genome. Indeed, very few intact LTR-retrotransposons share 100 % sequence similarity between 5′ to 3′ LTRs (Fig.…”
Section: Discussioncontrasting
confidence: 93%
“…Though several studies report recent LTR-retrotransposon bursts in related grasses (Piegu et al 2006;Bennetzen et al 2012;Senerchia et al 2013), we did not detect a large amount of recent activity in the Sorghum reference genome. Indeed, very few intact LTR-retrotransposons share 100 % sequence similarity between 5′ to 3′ LTRs (Fig.…”
Section: Discussioncontrasting
confidence: 93%
“…Comparison of genetic variation around LTR‐RT loci (SSAP) and random sequences (AFLP) exhibited clear patterns of introgression across hybrid zones, but showed discrepant patterns of variation that are matching predictions based on the dynamics of LTR‐RTs in progenitors (Senerchia et al . , ). Quiescent LTR‐RTs such as Egug revealed nonsignificant specific admixture, indicating introgression similar to AFLP sequences (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…oGenomes of wild wheats contain 80% of interspersed repeats and have been greatly affected by the differential dynamics of specific LTR‐RTs (Senerchia et al . , ). A few LTR‐RTs such as Egug have been reported as quiescent in both A. geniculata and A. triuncialis , and can thus be expected to segregate beyond species boundaries as random sequences.…”
Section: Introductionmentioning
confidence: 99%
“…tauschii (D). Senerchia et al (2013) suggested that the sequencing of 2.5 % of Aegilops genomes was sufficient to survey genome-wide copies of several abundant TEs, including characteristic families from pericentromeric regions. Our SLAF method surveyed with short reads can thus be applied to abundant TEs of any genome sequencing for identifying and quantifying the TE families within genomes.…”
Section: Discussionmentioning
confidence: 99%